Impact of Liquidity Ratio, Dividend on Share Price: A Study of Food and Allied, Engineering, and Pharmaceuticals and Chemicals Industries in Bangladesh - Md. Raihan Habib (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2024)
This research focused to analyze impact of liquidity ratios, dividend on share price of three industries. The industries are engineering, food and allied, pharmaceuticals and chemicals. Total sample size for this research is 425. A number of total 85 companies’ data has been collected. Five years of data has been collected from annual reports and lanka bangla. The duration of the year is 2016-2020. Current ratio and share price has significant negative relationship. Also, there is negative relationship between quick ratio and share price. On the other hand, there is strongly positive relationship between cash ratio and share price. In addition, there is significant positive relationship between dividend and share price. The research method used is a quantitative method using Secondary data has been used for conducting this research. It is the core limitation of this research. Besides we could not be able to find some companies data. And sample size has decreased because of that. This research wanted to find out the relationship between share price with liquidity ratios and dividend. Now general people, investors, shareholders, creditors can take decisions based on our study’s findings. We hope this research will be helpful for both academicians and professionals.